2007
DOI: 10.1086/516790
|View full text |Cite
|
Sign up to set email alerts
|

CD14−550 C/T, Which Is Related to the Serum Level of Soluble CD14, Is Associated with the Development of Respiratory Syncytial Virus Bronchiolitis in the Japanese Population

Abstract: CD14 -550 C/T, which is related to the serum level of sCD14, is associated with the development of RSV bronchiolitis in the Japanese population. This study's results indicate that, in different ethnic groups, different genetic factors contribute to the development of RSV bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 27 publications
2
44
1
2
Order By: Relevance
“…To determine whether CD14 affected RSV disease severity, we asked whether the CD14 C-159T and CD14 C-550T SNPs were also associated with RSV bronchiolitis (Figure 1, F and G, and Supplemental Table 8). Allelic frequencies for both SNPs were in Hardy-Weinberg equilibrium and did not differ from those reported previously (16,17,31). Unlike TLR4 Asp299Gly, CD14 C-159T and CD14 C-550T did not affect RSV disease severity.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…To determine whether CD14 affected RSV disease severity, we asked whether the CD14 C-159T and CD14 C-550T SNPs were also associated with RSV bronchiolitis (Figure 1, F and G, and Supplemental Table 8). Allelic frequencies for both SNPs were in Hardy-Weinberg equilibrium and did not differ from those reported previously (16,17,31). Unlike TLR4 Asp299Gly, CD14 C-159T and CD14 C-550T did not affect RSV disease severity.…”
Section: Introductionsupporting
confidence: 61%
“…Control subjects included infants with oxygen saturation at or above 93% while breathing room air. In addition, these criteria allow comparison with numerous previous studies (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral, host, and environmental factors probably all contribute to this variable disease expression, but the relative roles of these factors in human RSV disease remain difficult to evaluate. A series of recent genetic association studies have suggested that polymorphisms in a range of genes encoding cytokines, chemokines, surfactant proteins, or toll-like receptors influence the disease phenotype in humans (1,8,19,21,23,35,45,52,57). However, it remains unclear how and to what extent these factors contribute to disease pathogenesis.…”
mentioning
confidence: 99%
“…Επίσης, ανάλογη µελέτη σε Ιάπωνες δεν πέτυχε να ανιχνεύσει τους δύο πολυµορφι-σµούς σε κανένα από τα εξεταζόµενα άτοµα [191].…”
Section: Tlr4 και Tlr2unclassified